Sacrifice and solidarity: a qualitative study of family experiences of death and bereavement in critical care settings during the pandemic. Issue 1 (19th January 2022) - Dennis, Brittany; Vanstone, Meredith; Swinton, Marilyn; Brandt Vegas, Daniel; Dionne, Joanna C; Cheung, Andrew; Clarke, France J; Hoad, Neala; Boyle, Anne; Huynh, Jessica; Toledo, Feli; Soth, Mark; et al.
Abstract : Background: Pandemic-related restrictions are expected to continue to shape end-of-life care and impact the experiences of dying hospitalised patients and their families. Objective: To understand families' experiences of loss and bereavement during and after the death of their loved one amidst the SARS-CoV-2 (COVID-19) pandemic. Design: Qualitative descriptive study. Setting: Three acute care units in a Canadian tertiary care hospital. Participants: Family members of 28 hospitalised patients who died from March–July 2020. Main outcome measures: Qualitative semistructured interviews conducted 6–16 months after patient death inquired about family experiences before and beyond the death of their loved one and garnered suggestions to improve end-of-life care. Results: Pandemic restrictions had consequences for families of dying hospitalised patients. Most family members described an attitude of acquiescence, some framing their experience as a sacrifice made for the public good. Families appreciated how clinicians engendered trust in the name of social solidarity while trying to mitigate the negative impact of family separation. However, fears about the patient's experience of isolation and changes to postmortem rituals also created despair and contributed to long-lasting grief. Conclusion: Profound loss and enduring grief were described by family members whose final connections to their loved one were constrained by pandemic circumstances. Families observed solidarity among clinical staff and experienced a sense of unity with staff, which alleviated some distress. Their suggestions to improve end-of-life care given pandemic restrictions included frequent, flexible communication, exceptions for family presence when safe, and targeted efforts to connect patients whose isolation is intensified by functional impairment or limited technological access. Trial registration number: NCT04602520 ; Results.